Effect of acupuncture on patients with chronic obstructive pulmonary disease: A multicenter randomized controlled trial - Jiansheng Li; Yang Xie; Yanjun Wang; Lei Wu; Xuefeng Yu; Li Bai; Suju Shao; Miao Zhou; Mingli Zhang; Xueqing Yu; Weihong Han; Xuanlin Li; et al. (Complementary Therapies in Medicine)
Background: Chronic obstructive pulmonary disease (COPD) is a common and frequently occurring disease that seriously endangers health, causing a heavy economic burden on patients and society. Acupuncture has been reported to have a therapeutic effect on patients with chronic obstructive pulmonary disease (COPD). However, compared with medications, it is difficult to identify a superior therapy. Therefore, the aim of this study was to evaluate the efficacy and safety of acupuncture, conventional drug and acupuncture plus conventional drug in the treatment of COPD. Methods: This was a multicenter, open-label randomized controlled trial (RCT) through a central randomization system. A total of 150 COPD patients were randomly assigned at a 1:1:1 ratio to the acupuncture group, conventional drug group or acupuncture plus conventional drug group for 12 weeks of treatment, followed by 12 weeks of untreated follow-up. The primary outcomes included the six-minute walk distance (6MWD) and St. George’s Respiratory Questionnaire (SGRQ), and the secondary outcomes included the modified Medical Research Council dyspnea scale (mMRC), acute exacerbation, lung function, and quality of life (COPD assessment test). Statistical analysis was conducted via SPSS software (version 26.0). Results: A total of 150 patients were included in the study, and 143 patients completed the trial. There were time effects, group effects and interaction effects in the three groups (P < 0.05). Compared with that in the conventional drug group, the 6MWD in the acupuncture plus conventional drug group increased significantly at 4, 8, and 12 weeks of treatment and at 12 weeks of follow-up. The difference was statistically significant (P < 0.05). The symptom scores, motor scores, impact scores and total SGRQ scores at different time points in the three groups tended to change with time, with a time effect (P < 0.05), and there was no group or interaction effect (P > 0.05). Among the secondary outcomes, there were time effects on the number of acute exacerbations, forced expiratory volume in one second (FEV1) and forced expiratory volume in one second/forced vital capacity (FEV1/FVC) at different time points in the three groups (P < 0.05). mMRC had time and group effects (P < 0.05). CAT had time effects, group effects and interaction effects (P < 0.05). Conclusions: Compared with the acupuncture group and the conventional drug group, the acupuncture plus conventional drug group was better at improving exercise ability, improving quality of life, and reducing dyspnea. It is safe and effective for the treatment of chronic obstructive pulmonary disease in the stable period, which can provide a reference for further related research.Trial registration:ClinicalTrials.gov, NCT03169504. Registered on 30 May 2017.